PENGEMBANGAN KELAPA SAWIT SEBAGAI BIOFUEL DAN PRODUKSI MINYAK SAWIT SERTA HAMBATANNYA - Supraniningsih, Juliati (MAJALAH ILMIAH WIDYA, 2012)
Global warming becomes an important issue nowadays. To decrease carbon emission and to stop climate changes in the formof global warming is one of Kyoto Protocol agreement as to find out alternative energy that can replace the need of fossil energy.The objective of this article is to discuss the palm plantations, the products and the obstacles of making the palm to become alternativeenergy. The conclusion are: (1) Three methods to get biofuel are from organic waste combustion, compost heap, and fermentationof anaerobe in biogas process from animal feces and fermentation of aerobe that produce bioetanol and biodiesel. (2) Crude-palmoil not only is used to make biofuel but also to make grease up to cosmetic. (3) Biofuel program has developed and increased theexpansion of palm plantation and it caused damages to the environment, especially the protected forest, forest that owned by the local,and national park that preserve plant and animal.